2017
DOI: 10.1002/jcla.22279
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐ENA antibody profiles in patients with hepatitis C virus infection

Abstract: The prevalence of anti-ENA antibodies was significantly higher in the patients with HCV infections than in the healthy controls. Other studies of anti-ENA profiles in patients with HCV infection have identified similar patterns of positivity for anti-SSA, anti-SSB, anti-dsDNA, anti-RNP, anti- Sm/RNP, Scl-70, centromere B, and anti-Sm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…ANA+ENA detection represents the measuring of a series of autoantibodies majorly antinuclear antibodies, which are closely related with many autoimmune diseases, and involved in the pathogenesis of many kinds of viruses 33,34 . Lately, Zhong et al revealed patients with autoimmune rheumatic disease might be more susceptible to COVID-19 infection than the general population 15 .…”
Section: Discussionmentioning
confidence: 99%
“…ANA+ENA detection represents the measuring of a series of autoantibodies majorly antinuclear antibodies, which are closely related with many autoimmune diseases, and involved in the pathogenesis of many kinds of viruses 33,34 . Lately, Zhong et al revealed patients with autoimmune rheumatic disease might be more susceptible to COVID-19 infection than the general population 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the clinical associations of ANA with rheumatic and non-rheumatic conditions, the relationship between these antibodies and specific disease manifestations is often unknown since their targets are predominantly intracellular and ubiquitously expressed [ 57 ].…”
Section: Auto-antibodies and Hcvmentioning
confidence: 99%
“…In conclusion, non-organ-specific humoral autoimmunity is significantly present in adult patients with 47,XXY, but not in patients with HGA. Because it is always clinically difficult to precisely diagnose a systemic autoimmune disease [22][23][24]31,33,35] and some autoimmune diseases, such as SLE, are more severe in these patients than in 46,XY men [37], the additional information from the presence of non-organ-specific autoantibodies is important, as it may strongly support the analysis of the clinical presentation and physical examination of each patient. As reported in the literature, the occurrence of these autoantibodies precedes the possible development and progression of most autoimmune disorders [47,48], which suggests the importance of screening non-organ-specific autoimmunity in Xchromosome aneuploidies in clinical practice to identify patients at risk of developing non-organ-specific autoimmune diseases.…”
Section: F I G U R Ementioning
confidence: 99%
“…These autoantibodies have high avidity and specificity and are widely used in the diagnosis and monitoring of SLE [30][31][32]. ENAs represent a large family of non-organ-and non-species-specific autoantibodies, the detection of which is of great importance in the laboratory diagnosis of systemic rheumatic autoimmune diseases [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%